(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Since Last few years Data in internet is growing tremendously which is coined as Big Data. This Big Data includes data collected from different sources and in different forms. In this paper different Data Forms, Characteristics and Pipeline Analysis of Big Data is explained. Our objective is to explain 6V’s of Big Data and Big Data Model. For Handling this big data there are different software’s are available in market. Among of all Hadoop is one of the popular Software. It is open source software used to store big data of large dataset across a commodity of clustered servers. Concept of HDFS and Map Reduce is being illustrated. Apart of that Hadoop Ecosystem with its supporting Apache software’s have been mentioned with their characteristics.